Anatomical and cellular localization of melatonin MT1 and MT2 receptors in the adult rat brain. Issue 4 (23rd March 2015) - Lacoste, Baptiste; Angeloni, Debora; Dominguez‐Lopez, Sergio; Calderoni, Sara; Mauro, Alessandro; Fraschini, Franco; Descarries, Laurent; Gobbi, Gabriella
Abstract The involvement of melatonin in mammalian brain pathophysiology has received growing interest, but information about the anatomical distribution of its two G‐protein‐coupled receptors, MT1 and MT2, remains elusive. In this study, using specific antibodies, we examined the precise distribution of both melatonin receptors immunoreactivity across the adult rat brain using light, confocal, and electron microscopy. Our results demonstrate a selective MT1 and MT2 localization on neuronal cell bodies and dendrites in numerous regions of the rat telencephalon, diencephalon, and mesencephalon. Confocal and ultrastructural examination confirmed the somatodendritic nature of MT1 and MT2 receptors, both being localized on neuronal membranes. Overall, striking differences were observed in the anatomical distribution pattern of MT1 and MT2 proteins, and the labeling often appeared complementary in regions displaying both receptors. Somadendrites labeled for MT1 were observed for instance in the retrosplenial cortex, the dentate gyrus of the hippocampus, the islands of Calleja, the medial habenula, the suprachiasmatic nucleus, the superior colliculus, the substantia nigra pars compacta, the dorsal raphe nucleus, and the pars tuberalis of the pituitary gland. Somadendrites endowed with MT2 receptors were mostly observed in the CA3 field of the hippocampus, the reticular thalamic nucleus, the supraoptic nucleus, the inferior colliculus, the substantia nigra pars reticulata, and the ventrolateral periaqueductal gray. Together, these data provide the first detailed neurocytological mapping of melatonin receptors in the adult rat brain, an essential prerequisite for a better understanding of melatonin distinct receptor function and neurophysiology.